Konsinyasi dan Efektivitas Hukum dalam Sengketa Pertambangan Rakyat Gorontalo - Potale, Rilla Miftahuljannah; Wantu, Fence M.; Bakung, Dolot Alhasni (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the basis of judges' considerations in decisions on illegal mining cases involving foreign nationals and their relevance to the effectiveness of the law in the context of consigning payments of Non-Tax State Revenue (PNBP). The study focuses on three interconnected legal instruments: Gorontalo District Court Decision No. 177/Pid.Sus/2022, Supreme Court Decision No. 1502 K/Pid.Sus/2023, and Gorontalo District Court Consignment Determination No. 1/Pdt.P-Kons/2023. The research method used is a normative legal approach supported by qualitative-descriptive analysis, which relies on the study of legislation, legal doctrines, and court decisions. The research findings indicate that the trial court's considerations at the first instance focused on proving the elements of the offense, while the Supreme Court emphasized the socio-economic legitimacy of small-scale mining activities that had not been formalized as a People's Mining Area (WPR), and rejected criminalization due to regulatory gaps. Furthermore, the court, thru a consignment ruling, proves its role as a harmonizing tool when the state's fiscal obligations must still be met even tho the technical collection mechanism is not yet available. These three legal products illustrate the harmony between legal certainty, the principle of justice, and utility, while also affirming that the effectiveness of law does not only depend on the existence of written norms, but also on the judiciary's sensitivity in responding to existing social and administrative realities.